IMPLEMENTASI KEBIJAKAN UNIVERSAL HEALTH COVERAGE UNTUK MENGATASI MASALAH KESEHATAN BAGI BAGI MASYARAKAT KURANG MAMPU DI KOTA SEMARANG - Siti Aisyah; Dyah Lituhayu; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Universal Health Coverage (UHC) is the government's effort to provide health service facilities to the community for free with premiums paid by the Regional Government through the Regional Budget. The research aims to analyze the implementation of the UHC policy, analyze the inhibiting and driving factors for the implementation of UHC in the city of Semarang. The research method uses descriptive qualitative. Source of data through interviews and documentation. The informant selection technique used purposive sampling. The implementation of UHC in the city of Semarang is regulated in Mayor Regulation Number 43 of 2017 concerning the Implementation of Health Insurance, the result is that the UHC program has not fully run well. There are problems at the Health Service UHC Service Counter experiencing a shortage of staff which results in an overlapping workload for officers and constraints on the automatic population verification data input due to the unstable website because there is no application that supports Dispendukcapil yet. Recommendations in the research are that the Health Office improves the quality and competence of employees and provides information and technology systems that support services to be more effective at UHC Service Counters and system or application innovations that integrate population data automatically with one NIK to register as UHC participants..